Saxagliptin Induces β-Cell Proliferation through Increasing Stromal Cell-Derived Factor-1α In Vivo and In Vitro - Li, Chun-Jun; Sun, Bei; Fang, Qian-Hua; Ding, Min; Xing, Yun-Zhi; Chen, Li-Ming; Yu, De-Min (Frontiers in Endocrinology, 2017)
Dipeptidyl peptidase-4 inhibitors, such as saxagliptin, have been reported to have beneficial effects on β-cell function, but the specific underlying mechanism remains unclear. Stromal cell-derived factor-1α (SDF-1α), a chemokine produced in multiple organs, has been considered as a crucial regulator in promoting β-cell survival. Here, we speculate that SDF-1α might mediate the effect of saxagliptin on improving β-cell function. After 12-week saxagliptin treatment in high fat diet/streptozotocin induced diabetic rats, significant improvements in pancreas insulin secretion capacity evaluated by hyperglycemia clamp and increased β-cell to α-cell areas ratio. Saxagliptin could significantly induce β-cell proliferation and upregulate the expression of proliferation related factors including c-myc and cyclind D1. The expression/activity of DPP-4 was significantly reduced and paralleled with the restoration of SDF-1α levels in the saxagliptin-treated diabetic rats, subsequently the key WNT signaling regulators, β-catenin and AKT, were activated. However, the effect of saxagliptin inducing β-cell proliferation was attenuated when we silenced the SDF-1α receptor (CXCR4) with RNAi in INS cell lines. Collectively, our data indicate that SDF-1α mediates the protective effect of saxagliptin on β-cell proliferation, suggesting that DPP-4 inhibitors have the potential role on delaying β-cell failure and SDF-1α could be a therapeutic target of β-cell regeneration.